TINDAK TUTUR ILOKUSI PADA NASKAH DRAMA THE KING AND ME KARYA HANIF KUREISHI - Tegar Pratama; Lusi Susilawati (Nusantara Hasana Journal, 2024)
This research aims to provide information on the types of illocutionary speech acts in the drama script The King and Me by Hanif Kueishi. The information which is obtained from the results of this research can be used as material to understand individual characteristics, such as social background, culture, or personality, which affects the use of illocutionary speech acts in other literary studies to understand how their application can be different depending on the context of the literary work itself. The data used in this research are the contents of the book in the form of the dialogue The King and Me, technique of collecting data is by taking data through simak and catat or “taking notes” method. The type of data which is used is objective data in the form of dialogue content in books in the form of dialogue data containing illocutionary utterances presented in the form of clear understanding and narrative. The analysis technique used in this research is the condensation, presentation and note-taking model. To find out data containing illocutionary utterances through analysis then presentation and note-taking into data which is divided into 5 big points. The results show that in the drama script The King and Me, the characters in the dialogue use various types of illocutionary speech acts, which depend on factors such as the context, purpose, and content of the speech. The suggestions in this research are that future research can examine the influence of the media on the use of illocutionary speech acts